Development Harmonisation of Mountain Resorts Ropeway and Tourist Infrastructures in the Republic of Slovenia - Sever, Drago (Promet - Traffic&Transportation)
Operation efficiency of mountain resort systems dependslargely on harmonious operation of the most important andtherefore most influential elements of ropeway transp01tationand tourist subsystems. Within the framework of a tourist subsystem,the extent and quality of tourist offer for long-stayingguests plays an essential role. Harm.onised development of theabove-mentioned elements ensures major utilisation and bettereconomic management of the entire system so that it may offerquality se1vices. First of all, the system enables permanent andenvironmentally friendly development of the systems that are asa rule in an absolutely sensitive alpine region.The article deals with some results of in-depth research onthe ropeway transportation system and the results of know-howtransfer into the actual environment of the Slovene mountainresorts.